The Economic Impact of AI Adoption: Measuring Productivity and Competitive Advantage in International Enterprises - Farrukh Avezov (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This article covers the economic impact analysis by quantitative assessment through implementing artificial intelligence technologies. It analyzes how AI solutions are Productively applied and the formation of sustainable competitive advantage in multinational corporations. The relevance of this study is justified by the rapid growth that exists in corporate and venture investments in AI, a forecast of global AI spending to reach USD 632 billion by 2028, and a need for companies to adapt business processes as fast as possible to keep them competitive in the international market. The novelty of the work lies in a comprehensive synthesis of industry statistics (CB Insights, IDC, McKinsey, PwC, OECD), resource‐based theory of the firm, and the concept of dynamic capabilities to explain sustainable advantages. The methodology includes descriptive and comparative analysis of financial metrics, macroeconomic forecasts of AI’s added value, and detailed case studies of implementations at Google, Amazon, Nike, and Starbucks. The significant results show that, in general, artificial intelligence raises firms’ labor productivity by 0–11%, improves Overall Equipment Effectiveness in manufacturing, quickens Time‐to‐Market, and increases Customer Lifetime Value in retail and services. Generative AI can add between 1.3% and 9.3% of revenue in different fields of business; also, the worldwide economic impact is approximated at USD 2.6–4.4 trillion per year. Sustainable competitive advantage emerges at the intersection of VRIN resources (unique data, algorithms, infrastructure) and firms’ ability to sense, seize, and transform new opportunities rapidly. At the same time, the key constraints are regulatory costs, the capital intensity of infrastructure, and the hype cycle effect. This article will be helpful for managers, strategists, and analysts of multinational corporations, as well as consultants and researchers assessing the economic efficiency and competitive benefits of AI implementation.